Lucene 4 cookbook : over 70 hands-on recipes to quickly and effectively integrate Lucene into your search application /: over 70 hands-on recipes to quickly and effectively integrate Lucene into your search application. (2015) - Ng, Edwood; Mohan, Vineeth
No abstract available